Hypothalamus-Olfactory System Crosstalk: Orexin A Immunostaining in Mice - Gascuel, Jean; Lemoine, Aleth; Rigault, Caroline; Datiche, Frédérique; Benani, Alexandre; Pénicaud, Luc; López-Mascaraque, Laura (Frontiers in Neuroanatomy, 2012)
It is well known that olfaction influences food intake, and conversely, that an individual’s nutritional status modulates olfactory sensitivity. However, what is still poorly understood is the neuronal correlate of this relationship, as well as the connections between the olfactory bulb and the hypothalamus. The goal of this report is to analyze the relationship between the olfactory bulb and hypothalamus, focusing on orexin A immunostaining, a hypothalamic neuropeptide that is thought to play a role in states of sleep/wakefulness. Interestingly, orexin A has also been described as a food intake stimulator. Such an effect may be due in part to the stimulation of the olfactory bulbar pathway. In rats, orexin positive cells are concentrated strictly in the lateral hypothalamus, while their projections invade nearly the entire brain including the olfactory system. Therefore, orexin appears to be a good candidate to play a pivotal role in connecting olfactory and hypothalamic pathways. So far, orexin has been described in rats, however, there is still a lack of information concerning its expression in the brains of adult and developing mice. In this context, we revisited the orexin A pattern in adult and developing mice using immunohistological methods and confocal microscopy. Besides minor differences, orexin A immunostaining in mice shares many features with those observed in rats. In the olfactory bulb, even though there are few orexin projections, they reach all the different layers of the olfactory bulb. In contrast to the presence of orexin projections in the main olfactory bulb, almost none have been found in the accessory olfactory bulb. The developmental expression of orexin A supports the hypothesis that orexin expression only appears post-natally.